Homothallism in Pseudoperonospora humuli. (21st March 2017) - Gent, D. H.; Cohen, Y.; Runge, F.
Abstract : The downy mildew pathogen, Pseudoperonospora humuli, forms oospores abundantly in diseased hop tissue. Diverse monosporangial isolates of P. humuli derived from samples collected in Japan, Germany and the USA readily formed oospores within hop leaves when inoculated singly, suggesting homothallism. Single zoospore isolates also readily formed oospores within hop leaves, further supporting the homothallic nature of this oomycete. The majority of oospores were deemed viable based on cytoplasm characteristics and plasmolysis assays. However, disease symptoms failed to develop when hop leaves were inoculated with newly formed oospores, even when oospore conditioning was attempted with treatment with potassium permanganate or β ‐glucuronidase/arylsulphatase, brief exposure to freezing temperature, or passage through an earthworm. Oospores derived from a monosporangial isolate of P. humuli that overwintered outdoors in infested leaves buried in soil also failed to cause downy mildew. Pseudoperonospora humuli is homothallic and oospores of the organism appear to require as yet unknown conditions to stimulate their germination and/or infection.